2015
DOI: 10.1111/jocn.12914
|View full text |Cite
|
Sign up to set email alerts
|

Learning to ensure patient safety in clinical settings: comparing Finnish and British nursing students’ perceptions

Abstract: Health care organisations and professionals with responsibilities for patient safety should seek to standardise the preparation of nursing students incorporating requisite international standards and benchmarks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
47
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(53 citation statements)
references
References 24 publications
5
47
0
Order By: Relevance
“…According to our findings, combining multiple teaching and learning strategies aimed at supporting nursing students to develop confidence on PS issues, by also developing a closer academic–clinical partnership, has been considered to increase immediate disclosure, and therefore, debriefing sessions on PS events (Wu, Enskär, Pua, Heng, & Wang, ). Moreover, it is also important to adopt well‐established teaching and learning methods for PS competence improvement by ensuring that PS disclosure is embodied among nursing professional standards, current legislation, and nursing responsibility (Tella et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…According to our findings, combining multiple teaching and learning strategies aimed at supporting nursing students to develop confidence on PS issues, by also developing a closer academic–clinical partnership, has been considered to increase immediate disclosure, and therefore, debriefing sessions on PS events (Wu, Enskär, Pua, Heng, & Wang, ). Moreover, it is also important to adopt well‐established teaching and learning methods for PS competence improvement by ensuring that PS disclosure is embodied among nursing professional standards, current legislation, and nursing responsibility (Tella et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, there is little empirical research in the field of health care specifically examining nationality as a factor in whistleblowing. Tella et al 124,129 found that UK nursing students considered themselves better prepared for reporting on problems in relation to patient safety than their Finnish counterparts, and Tabak et al 130 noted that knowledge of the concept of whistleblowing was relatively underdeveloped in Israel compared with the UK, although it was reported that the same moral imperative to care for patients existed in both countries. Skivenes and Trygstad 131 discussed research carried out by the Norwegian government on whistleblowing in the broader public sector, which suggests that, in contrast to the findings of many international studies, Norwegians generally had very positive experiences of whistleblowing, reporting constructive responses when reporting problems to employers.…”
Section: Regional and National Culturementioning
confidence: 99%
“…Enabling trainee health-care workers to judge where the line is drawn in terms of delineating poor care from adequate care is considered fundamental to nurse training, with many authors contributing to the general discussion on this. 96,104,122,124,129 Ion et al 86 argue that student nurses often lack confidence in their own judgement, and Bickhoff et al…”
Section: Boundary Definitionsmentioning
confidence: 99%
See 2 more Smart Citations